Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1097/sla.0000000000003449
|View full text |Cite
|
Sign up to set email alerts
|

Resection of Cavity Shave Margins in Stage 0–III Breast Cancer Patients Undergoing Breast Conserving Surgery

Abstract: Objective: Single-center studies have demonstrated that resection of cavity shave margins (CSM) halves the rate of positive margins and re-excision in breast cancer patients undergoing partial mastectomy (PM). We sought to determine if these findings were externally generalizable across practice settings. Methods: In this multicenter randomized controlled trial occurring in 9 centers across the United States, stage 0–III breast cancer patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 19 publications
(58 reference statements)
1
28
1
4
Order By: Relevance
“…This decision influences the amount of tissue a surgeon takes during original BCS. In studies by Dupont and colleagues 11 and Chapgar and colleagues 2 with intraoperative randomization, systematic CSM resulted in a larger total volume of tissue excised; in our study, without intraoperative randomization, the volume of tissue excised in the no shave margins and systematic CSM groups did not differ.…”
Section: Resultscontrasting
confidence: 46%
See 2 more Smart Citations
“…This decision influences the amount of tissue a surgeon takes during original BCS. In studies by Dupont and colleagues 11 and Chapgar and colleagues 2 with intraoperative randomization, systematic CSM resulted in a larger total volume of tissue excised; in our study, without intraoperative randomization, the volume of tissue excised in the no shave margins and systematic CSM groups did not differ.…”
Section: Resultscontrasting
confidence: 46%
“…A study by Dupont et al indicated a reduction in positive margin rate from 18.5% in the no shave group to 5.8% in the shave group in a subgroup analysis of three surgeons with positive margin rates less than 25% prior to randomization 11 . However, in this study, as well as in the study by Chapgar and colleagues, 2 randomization occurred intraoperatively after the surgeon had taken what was felt to be an adequate specimen.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…43 Besides, several other studies pointed out CS as an effective technique to avoid re-excisions in the adjuvant setting. 44,45 However, data about upfront systemic therapy are limited to retrospective cohort series, reporting the status of CS as the only independent predictive factor for loco-regional recurrence after NAC. 46 In accordance, IOUS successfully ruled out margin positivity in all patients in our protocol where CS is a routine and no-ink-on-tumor is regarded as safe margin after NAC.…”
Section: Discussionmentioning
confidence: 99%
“…Landercasper et al reported surgeon performed US, NAC, and CSs as the actionable processes to decrease reoperations after BCS 43 . Besides, several other studies pointed out CS as an effective technique to avoid re‐excisions in the adjuvant setting 44,45 . However, data about upfront systemic therapy are limited to retrospective cohort series, reporting the status of CS as the only independent predictive factor for loco‐regional recurrence after NAC 46 .…”
Section: Discussionmentioning
confidence: 99%